PENDAPATAN DAN NILAI TAMBAH USAHA KOPI BUBUK ROBUSTA DI KABUPATEN LEBONG (STUDI KASUS PADA USAHA KOPI BUBUK CAP PADI) - Reswita, Reswita (Jurnal AGRISEP, 2016)
Robusta coffee is one of the largest plantation crops in Lebong. To increase the economic value of coffee is to do further processing into products that can be consumed directly. Processing can increase the value-added products, increase the shelf life, and increase profits. The purpose of this study was to determine the income and valueadded business processing rice coffee into the ground coffee in the coffee business in the district Rice Powder Cap North Labong Lebong. Operating revenues rice processing coffee into the ground coffee in the coffee business Cap Rice Rp. 4,266,080.18 in one production process. Value added processing businesses into the ground coffee coffee rice Rp. 10346.67 / kg with added value ratio of 32.08% in one production process.